El yacimiento achelense de As Gándaras de Budiño: la industria en facies fluviales - Méndez Quintas, Eduardo (Complutum, 2007)
As Gándaras de Budiño is one of the most knows acheulian site in the Iberian Peninsula, although there aren’t any recent publications about its industry, stratigraphy context or chronology. In this article we will study the unpublished lithic material found in fluvial deposits excavated by Julio Vidal Encinas at the beginning of the 80s. This assemblage shows all characteristic of the acheulian industry of the peninsular Middle Pleistocene. The sediments which contain the industry have been formed in medium energy environments. The few disturbances of the materials suggest that these are repose in a similar position at the original.